Analysis of User Acceptance of Bus Ticket Application Using a Modified UTAUT Model (Case Study: RedBus Application) - Bella Trinanda Sanni; Anita Wulansari; Rafika Rahmawati (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2025)
The advancement of digital technology has driven the adoption of mobile-based transportation applications, such as RedBus—an online bus ticket booking platform. Despite experiencing significant growth, RedBus faces challenges in user acceptance, marked by a decline in positive reviews and an increase in user complaints during 2023–2024. Therefore, it is crucial to understand the factors that influence user acceptance and their decision to continue using the application. This study analyzes these factors using a modified UTAUT model by incorporating external variables such as Habit, Perceived Cost, Customer Satisfaction, and Repurchase Intention. A quantitative analysis was conducted using the PLS-SEM method with SmartPLS 3.0 software, involving 413 respondents selected through purposive sampling. The results show that nine hypotheses were accepted while four were rejected. The variables Performance Expectancy and Facilitating Conditions significantly influenced Trust, whereas Effort Expectancy and Social Influence did not. Performance Expectancy, Effort Expectancy, and Facilitating Conditions had a significant impact on Purchase Decision, while Social Influence did not. Trust was found to mediate the relationship between several variables and Purchase Decision, which in turn affected Customer Satisfaction. Perceived Cost and Customer Satisfaction influenced Repurchase Intention, while Habit had no significant effect. These findings highlight the importance of improving service quality, ease of access, and user trust to maintain customer loyalty toward the RedBus application.